INTERVENSI PEKERJAAN SOSIAL UNTUK MAKASSAR DAMAI SEJAHTERA (Kasus Konflik Antar Warga Di Kel.Balang Baru Kota Makassar) - Wahab, Abd. (Jurnal Berita Sosial, 2018)
The rise of social conflict that resulted in social violence in Makassar city in the form of brawl between citizens, teenagers, inter-village brawl, house burning and so on, triggered by religious, ethnic, group, democratic, which is closely related to poverty and underdevelopment.soclusi offered in megatasi it with social work intervention. Keywords: Social Work Intervention, Intercommunity Conflict.